Toyota fifty years in motion an autobiography by the chairman - Toyoda, Eiji (Kodansha International, 1987)
This books is about the rich and multifaceted aacount of the life of one man - Eiji Toyoda - whose achievements and success parallel the growth and properity of both Toyota Motor Corporation and the automobile industry in general in Japan.